Gambaran Histopatologi Hepar Mencit (Mus musculus Balb/C) yang Diinfeksi dengan Plasmodium berghei - Hanifah Putri Dwiridal; Adrial Adrial; Eryati Darwin (Fakultas Kedokteran, Universitas Andalas, 2022)
Background: The most common cause of death by malaria in Indonesia is Plasmodium falciparum, which is analogous to Plasmodium berghei, which lives as a parasite in the liver of mice. The damage caused is seen in severe hepatocyte cell damage, which can be prevented by immunization, but the right type of immunization has not been found. Objective: This study aims to see whether immunization with Anopheles sundaicus salivary gland extract in mice can reduce liver damage in mice that have been infected with Plasmodium berghei. Methods: This research was conducted at the Anatomical Pathology Laboratory, Faculty of Medicine, Andalas University, from May - September 2020. The research method was descriptive with a quantitative approach. View and compare the histopathological picture of the liver of mice, which were infected with Plasmodium berghei after being immunized with Anopheles sundaicus salivary gland extract, in the pellet extract and supernatant extract groups, and the control group who were not immunized. The preparations were viewed using a microscope (Binocular Olympus BX 51 DIC), the number of hepatocytes was counted using the Image J application and the percentage of damage was calculated using the formula by Baldatina (2008). Results: The percentage of hepatocyte cell damage in the mencit control group was 96.27%, pellet extract 88.88% and supernatan extract 85.93%. Conclusion: The highest percentage of hepatocyte cell damage was found in the mencit control group and the lowest damage percentage in the supernatan extract group.